Heterogenność kliniczna zespołu Kabuki (zespół Niikawy i Kurokiego) na podstawie opisu przypadku 15-letniej pacjentki z nawykowym zwichnięciem rzepek - Błoch, Michał; Śmigiel, Robert (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Kabuki Syndrome (KS) is a rare genetic disease affecting about 1 in 30,000-86,000 live births. KS is characterized by the appearance of the distinctive dysmorphic features and coexisting congenital disorders. The majority of patients are diagnosed with mild and moderate intellectual disabilities. The clinical picture of the KS consists of skeletal disorders, for example, joints hypermobility. One such described patient shows intellectual norm which allows her to be educated in public school with the standard curriculum. Distinctive dysmorphic features appeared in early childhood of the patient. During the molecular diagnosis, when the patient was 15, a mutation of the gene KMT2D was con¬firmed. Because of double luxation of the patella of the patient, three surgeries that failed to stabilize the knee joint were performed. The distinctive and clear dysmorphy of the face in the KS allows to quickly confirm the diagnosis of the KS. Children with KS need multidisciplinary medical care. In case of occurrence of motor problems, the intensive rehabilitation program and orthopedic services are necessary.